Legal review on Halal labelling of Malaysian pharmaceutical products / Muhammad Azril Roslan and Norazlina Abdul Aziz - Roslan, Muhammad Azril; Abdul Aziz, Norazlina (Universiti Teknologi MARA, Negeri Sembilan, 2023)
The obligation of a Muslim to consume halal food derives from the Holy Quran, and the guidance of the Prophet Muhammad SAW serves as a guideline for humankind in achieving success and tranquillity of soul here and hereafter. “He hath forbidden you only carrion, and blood, and swine flesh, and that which hath been immolated to (the name of) any other than Allah. But he who is driven by necessity, neither craving nor transgressing, It Is no sin for him. Lol Allah Is Forgiving and Merciful.” (Quran, 2:173) The Prophet said, “The lawful Is what Allah has made lawful In HIs Book and the unlawful Is what Allah has made unlawful His book. Whatever He has been silent over has been pardoned.” Sunan Ibn Majah (3367) A statistic in 2021 shows that the global Muslim population is estimated to be approximately 1.9 billion Muslims today, making up 26% of the world's population. Halal product is no longer confined to Muslim consumers, as reports show that non-Muslims have acknowledged halal products because of the safety and hygienic aspect of the product. Halal products denote high quality, safe, and Shariah compliance. Previously, the authority was not in favour of certifying halal for drugs or pharmaceutical products. Producers and manufacturers opting not to label their products because halal is not mandatory to be disclosed although this scenario is against the spirit of rights to information accorded to the consumers.